Can Readable Sustainability Reports Mitigate Greenwashing's Market Consequences? - Dewi Ratnawati; Linda Ayu Wulandari; Prima Tri Puspita; Nur Aisyah Ramadhani; Deden Tarmidi (International Journal of Management Science and Information Technology, 2026)
The growing importance of sustainability issues has increased investors’ attention toward the credibility and quality of corporate sustainability disclosures. This study aims to examine the effects of greenwashing, foreign ownership, and profitability on market valuation and to investigate whether sustainability report readability moderates these relationships. The study contributes to the sustainability and capital market literature by exploring the role of readability in mitigating the market consequences of greenwashing within the energy sector. Using a quantitative approach, this research analyzes panel data from 43 energy companies listed on the Indonesia Stock Exchange during 2021–2024, resulting in 172 firm-year observations. Data was obtained from annual reports, sustainability reports, and audited financial statements. Panel data regression and Moderated Regression Analysis (MRA) were employed to test the proposed hypotheses. The findings reveal that greenwashing, foreign ownership, and profitability significantly affect market valuation. Sustainability report readability is found to weaken the relationship between greenwashing and market valuation, indicating that more readable sustainability disclosures help investors evaluate environmental claims more critically. However, readability does not moderate the relationships between foreign ownership and market valuation or between profitability and market valuation, although it directly contributes to market valuation as a predictor variable. These findings extend Signaling Theory by highlighting the importance of disclosure readability in reducing information asymmetry and improving the credibility of sustainability communication. The study suggests that firms should improve the clarity of sustainability disclosures to enhance transparency and support informed investment decisions.